Evaluation of Lower Urinary Tract Symptoms in Children Exposed to Sexual Abuse - Yildirim, Ali; Uluocak, Nihat; Atilgan, Dogan; Ozcetin, Mustafa; Erdemir, Fikret; Boztepe, Ozgur (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To evaluate the lower urinary tract symptoms (LUTS) in children that are exposed to sexual abuse. Materials and Methods: Fifty-two patients, including 8 male and 44 female children/adolescents presented with sexual abuse to the outpatient clinics were evaluated retrospectively (group 1). In group 1, the subjects were categorized into sexual touch (n = 35) and sexual penetration (n = 17). All the patients were evaluated with a detailed medical history, physical examination, and a dysfunctional voiding and incontinence scoring system questionnaire. Thirty age-matched children were evaluated as a control group (group 2). Results: The mean age of the patients was 12.2 ± 3.6 years and 12.0 ± 4.5 years in groups 1 and 2, respectively (P = .848). The mean age of the subjects in sexual touch and sexual penetration groups was 10.8 ± 3.6 years and 14.9 ± 1.5 years, respectively. The difference between sexual touch and sexual penetration groups was statistically significant (P = .0001). The incontinence rate was 30.76% and 23.3% in groups 1 and 2, respectively. This difference was not statistically significant (P = .640). The rates of daytime incontinence, nocturnal enuresis, diurnal incontinence, urgency, and continence maneuvers were 25.7%, 17.1%, 22.9%, 42.9%, and 20%, respectively, in sexual touch group, while they were found to be 5.9%, 0%, 0%, 17.6%, and 5.9%, respectively, in sexual penetration group. Conclusion: Although a significant association was not detected between sexual abuse and LUTS, it was seen that LUTS, such as urinary incontinence and urgency, were higher in children exposed to sexual abuse than the control group.